Archaeological Evidence for the Settlement Enterprises of the Hasmonean House in the Districts of Ofaraim, Lod and Ramataim - Dar, Shimʿon (Liber annuus, 2018)
The paper describes a dozen archaeological sites excavated in the ancient districts of Ofaraim, Lod, and Ramataim in recent years. These districts were ceded to the Hasmonean rulers of Judea by Demetrius II (145-140 BCE), the troubled Seleucid king. Prior to the excavations, only historical sources were available for scholars to reconstruct the actual process described in 1 Macc 11:32-34. The excavations revealed many small villages and farmsteads established by the Hasmonean rulers, mainly from John Hyrcanus I (134-104 BCE) and onward. The process of settlement continued until the Herodian period. In the excavated sites, many agricultural installations were unearthed: mikvaot, Jewish stone vessels, coins of the Hasmonean rulers, and synagogues in the larger settlements. During the two revolts against Rome, many of the settlements were destroyed and abandoned, mainly after the Bar-Kokhba war (132-136 CE). After being desolate for some generations, they were settled again by non-Jewish populations.